Therapeutic potentials of marine-derived nutrients: Exploring the role of fish eggs and meat in disease prevention and health promotion - Iqbal, Tasawar; Altaf, Sidra (Universitas Malikussaleh, 2025)
This article is a narrative literature review aimed at synthesizing current scientific knowledge on the nutritional and therapeutic properties of fish eggs and meat. Fish products, particularly fish eggs (roe) and meat, are rich in essential macronutrients, micronutrients, and bioactive compounds, such as omega-3 fatty acids, proteins, vitamins (D, B12, A), and minerals (iodine, selenium, phosphorus). These nutrients are associated with numerous health benefits, including cardiovascular protection, cognitive enhancement, anti-inflammatory effects, and improved joint health. The review also highlights the potential of fish-derived peptides, phospholipids, and antioxidants in modulating immune function and preventing chronic diseases such as cancer, diabetes, and rheumatoid arthritis. Moreover, the bioavailability of these nutrients, as influenced by cooking methods and supplements, is discussed about optimizing their health benefits. Sustainability and safety concerns, particularly regarding contaminants like mercury and polychlorinated biphenyls are also addressed, with a focus on ethical harvesting and the environmental impact of fishing practices. Emerging research into fish-based nutraceuticals, functional foods, and innovative drug delivery systems, such as fish-based nanocarriers opens new avenues for enhancing human health. Biotechnological advancements, such as fermentation and hydrolysis, further enhance the bioactive potential of fish products. Overall, fish eggs and meat represent a valuable component of a health-promoting diet, offering significant therapeutic benefits. Future research should focus on sustainable sourcing, maximizing nutrient bioavailability, and further exploring the potential of fish products in disease prevention and treatment.